P436 Ileal pouch-anal anastomosis with fluorescence angiography: Initial experience and potential application. (16th January 2018) - Spinelli, A; Kotze, P G; Carvello, M; Di Candido, F; Buchs, N; Ris, F
Abstract: Background: There are currently no descriptions of the use of fluorescence imaging during pouch construction. The aim of this study is to demonstrate the feasibility and the initial results of the use of fluorescence imaging with indocyanine green in ileal pouch-anal anastomosis. Methods: Retrospective study of a prospectively maintained database of patients submitted to ileal pouch-anal anastomosis. Settings: two referral centres, one from Italy and other from Switzerland. Patients: 32 patients (25 with ulcerative colitis and 7 with familial adenomatous polyposis). Interventions: minimally invasive ileal pouch-anal anastomosis procedures with the use of fluorescence imaging guidance to reduce tension and gain mesenteric length. Main outcome measures: demographic characteristics (age at surgery, gender), body mass index and approach (two- or three-stage). Perioperative data, such as operative time, conversion to laparotomy and the need for ileocolic vessels ligation were also checked. Length of hospital stay, Clavien-Dindo early postoperative complications, readmission and the need for reoperation were additionally analysed. Results: Twenty-one men and 11 women, with a median body mass index of 22 (15–36) were included. Twelve patients had two-stage procedures and 20 had three stage. Proctectomy was performed transanally in 19 and transabdominally in 13 cases. Safe ligation of ileocolic vessels after fluorescence was performed in 15 of 32 (47%) patients. The majority of patients (60%) had no postoperative complications. Six patients had Clavien-Dindo I and 6 had Clavien-Dindo II complications. One patient had a IIIb complication and underwent reoperation. There were no leaks, readmissions or mortality in the current series. Conclusions: Fluorescence imaging in minimally invasive ileal pouch-anal anastomosis is feasible, with low complication rates, and may impact in a reduction of leaks and pouchitis by reducing ischaemia. A prospective comparative trial in pouch construction using or not fluorescence is warranted.